Asynchrony in individual and subpopulation fecundity stabilizes reproductive output of an alpine plant population. Issue 4 (11th March 2019) - Waddle, Ellen; Piedrahita, Lucas R.; Hall, Elijah S.; Kendziorski, Grace; Morris, William F.; DeMarche, Megan L.; Doak, Daniel F.
Abstract: Population‐wide outcomes such as abundance, reproductive output, or mean survival can be stabilized by non‐synchronous variation in the performance of individuals or subpopulations. Such "portfolio effects" have been increasingly documented at the scale of subpopulations and are thought to play an important role in generating stability of population phenomena in the face of environmental variation. However, few studies quantify the strength and origin of portfolio effects at the finer scale of individuals. We used 16 yr of fruit production and climate data for an alpine plant to dissect the scale of portfolio effects in reproduction, as well as the contribution of individual traits including size and flowering time in driving reproductive output. Asynchrony in reproductive success substantially reduces variation in population‐level reproductive output, with approximately one‐fourth of this stabilizing effect arising from individual differences, mostly not those characterized by measured traits, and approximately three‐fourths from asynchrony across subpopulations. These results emphasize the different scales and causes of portfolio effects. The decomposition for portfolio effects we provide can facilitate similar breakdowns of the strength and causes of these effects in other systems.